Persepsi Mahasiswa FIKOM dan FISIP UPDM (B) Terhadap Perawatan Ortodonti oleh Dokter Gigi Umum dan Spesialis Ortodonti - Annisa Noer Asyifa; Diandra Alya Sarahita; Pricillia Priska Sianita (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Ortodontic treatment is an important effort to improve dentocraniofacial structure in both children and adults. However, public perception regarding ortodontic treatment by general dentists and specialist ortodontists still needs to be better understood. This study aims to examine the perceptions of FIKOM and FISIP UPDM(B) students toward ortodontic treatment. This is an analytical study with a cross-sectional design conducted online. The research subjects were 501 students from FIKOM and FISIP UPDM(B). The study shows that the majority of FIKOM and FISIP UPDM(B) students tend to trust specialist dentists more for their ortodontic treatment. The research indicates that FIKOM and FISIP UPDM(B) students have greater trust in ortodontic treatment provided by specialists due to their perceived expertise. Although awareness of the importance of specialization has increased, some still receive ortodontic treatment from general dentists.